Riding the Wave : An East Asian Miracle for the 21st Century - World Bank (Washington, DC: World Bank, 2017)
Developing East Asia has led the way in showing how rapid and broadly shared growth can lift millions out of poverty. And, as this book shows, the region has achieved even more: the wave of prosperity across the region since the 1980s has lifted three out of five of its citizens into economic security, where their risk of falling into poverty is minimal. Alongside this, a solid middle class has emerged in most countries. But these successes do not guarantee that inclusive growth--growth that reduces poverty and delivers upward mobility and economic security for all--is assured. The region has become more diverse, with progress varying across countries and extreme poverty increasingly concentrated among specific groups. Roughly a fifth of the region's population still remains at risk of falling into poverty and prospects for upward mobility are seen as increasingly elusive across the income distribution, reflecting a growing concentration of income and wealth and limited access to basic social services. Challenges old and new, including rapid aging and less certain growth prospects, are also increasing the premium on economic security for all. Riding the Wave is about how countries across the region can effectively confront these challenges and achieve inclusive growth.